2011
DOI: 10.2967/jnumed.110.087072
|View full text |Cite
|
Sign up to set email alerts
|

PET of Aromatase in Gastric Parietal Cells Using 11C-Vorozole

Abstract: Aromatase is a rate-limiting enzyme for estrogen biosynthesis and has been implicated in pathophysiological states of various diseases via estrogen production. This enzyme is known to be widely distributed in extragonadal and gonadal tissues including the stomach. In contrast to circulating estrogen, the functional role of gastric aromatase/estrogen has not been elucidated in detail, because there is no efficient methodology to investigate spatiotemporal changes of gastric aromatase/ estrogen in vivo. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
(45 reference statements)
3
24
0
Order By: Relevance
“…Prominent liver uptake was also seen across species. However, the high uptake in rat stomach reported by Ozawa et al (2011) was not seen in baboons or humans. Tracer uptake in the majority of most other peripheral organs, including bone, kidney, muscle, heart and lung, was uniformly low across species.…”
Section: Relationship Between In Vivo and In Vitro Studies Of Arommentioning
confidence: 81%
See 2 more Smart Citations
“…Prominent liver uptake was also seen across species. However, the high uptake in rat stomach reported by Ozawa et al (2011) was not seen in baboons or humans. Tracer uptake in the majority of most other peripheral organs, including bone, kidney, muscle, heart and lung, was uniformly low across species.…”
Section: Relationship Between In Vivo and In Vitro Studies Of Arommentioning
confidence: 81%
“…In vivo visualization of aromatase in rats was performed using microPET and [ 11 C]-vorozole (Ozawa et al, 2011; Kim et al, 2009). High accumulation of [ 11 C]vorozole was detected in the stomach and the adrenal glands.…”
Section: In Vivo Visualization Of Aromatase With Positron Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, aromatase imaging might be possible. An aromatase PET tracer is in preclinical development (Ozawa et al, 2011;Takahashi et al, 2014), although not for the purpose of breast cancer research. ER expression can be determined by 18 F-fluoroestradiol ( 18 F-FES) PET.…”
Section: E2 -Prediction Of Treatment Responsementioning
confidence: 99%
“…Recent studies have also demonstrated that stomach parietal cells abundantly express aromatase, a key enzyme for the production of sex steroids, and catalyze the final step of the biosynthetic pathway of estrogen [16]. Though gastric aromatase/estrogen has been implicated in several pathophysiological states, such as liver regeneration and feminization, by acting as a local regulator of the gastrohepatic axis, its functional role has still to be elucidated.…”
mentioning
confidence: 99%